Evaluation of Prognostic Factors Following Flow-Cytometric DNA Analysis after Cytokeratin Labelling: II. Cervical and Endometrial Cancer - Pauline Wimberger; Peter Hillemanns; Thomas Kapsner; Hermann Hepp; Rainer Kimmig (Analytical Cellular Pathology)
In gynecologic oncology valid prognostic factors are necessary to define biologically similar subgroups for analysis of therapeutic efficacy. This study is the first published prospective study concerning prognostic significance of DNA ploidy and S‐phase fraction in cervical and endometrial cancer following enrichment of tumor cells by cytokeratin labelling. Epithelial cells were labeled by FITC‐conjugated cytokeratin antibody (CK 5, 6, 8, and CK 17) prior to flow cytometric cell cycle analysis in 91 specimens of cervical cancer and 73 samples of endometrial cancer. In cervical cancer neither DNA‐ploidy nor S‐phase fraction were relevant prognostic parameters. But CV of the G0G1‐peak showed prognostic relevance in cervical cancer cells, even in multivariate analysis. This interesting observation, however, seems to have no therapeutic consequence due to the small discrimination capacity of CV. In endometrial carcinoma, gross DNA‐aneuploidy (DNA‐index > 1.3) and a high percentage of proliferating cells (>75th percentile) were univariate and multivariate highly significant prognostic factors for recurrence‐free survival. Especially DNA‐aneuploidy (DI>1.3) is one of the most important independent molecular biological prognostic factors. While diagnostic curettage we could identify risk patients even preoperatively by determination of the prognostic factors like histologic tumor type, grading, cervical involvement and DNA‐ploidy. Thereby these patients could be treated primarily in an oncologic center. In conclusion, our investigations showed that the determination of DNA‐ploidy should be done in endometrial carcinoma. In cervical cancer no clinical significance for determination of DNA‐parameters was found.